C programming : test your skills - Kamthane, Ashok N. (Pearson : Dorling Kindersley (India), 2010)
C Programming: Test Your Skills is specifically designed to be used as the supplementary resource for learning C Programming. It is ideal for self practice or test preparation and hones one's problem solving abilities through varieties of exercises.